Perspectives on active and inhibitive self-regulation relating to the deliberate practice activities of sport experts - Tedesqui, R. A. B.; Young, B. W. (Talent Development & Excellence, 2015)
On the long road to expertise, individuals must constantly negotiate motivational and effort constraints to deliberate practice (Ericsson et al., 1993). We draw on two different self-regulation theories to explore how athletes engage in more deliberate practice, and remain resilient during such activities. We discuss how a social-cognitive self-regulated learning model (Zimmerman, 2006) can be complemented by a strength model (Baumeister et al., 2007) to better understand experts` deliberate practice processes. Whereas the former model accounts for active pursuit of learning activities towards long-term goals, the latter model affords a unique examination of inhibitive self-control processes that enable experts to remain resilient during difficult practice. Finally, we identify research avenues that may advance the strength model as a novel conceptualization of expert self-regulation in sport.